Extraction and Composition of Nutmeg’s Essential Oils (Myristica fragrans Houtt.) Based on Seed Skin Color - Makin, Florian Mayesti Prima Remba; ., Welsiliana; Liunokas, Angreni Beaktris (Metamorfosa: Journal of Biological Sciences; Vol 9 No 2 (2022), 2022)
Nutmeg ( Myristica fragrans Houtt.) is native to Indonesia. One of the nutmeg products that are traded and exported is seeds. Nutmeg or what is commonly called nutmeg is in great demand because it contains many aromatic compounds in the form of essential oils. This study aims to extract and determine the composition of seed essential oils based on differences in seed coat color. Fresh samples were extracted and analyzed using GC-MS. The results showed that twelve compounds were identified in B1 and eleven seed compounds of B2 which were dominated by monoterpenes, respectively 85,76% and 80,56%; the rest are aromatic phenol-ether compounds. The dominant monoterpenes of B1 and B2 seeds, are sabinene (48,57%; 46,38%), ?-pinene (13,86%; 12,45%), and ?-pinene (13,36%; 12, 36%). Aromatic phenol-ether compounds such as myristicin (11,42%) and eugenol (0,62%) for B1 seeds and myristicin (16,50%) and metoksieugenol (0,92%) for B2 seeds. Nutmeg essential oil is dominated by monoterpenes and a few aromatic phenol-ether compounds.   Keywords : nutmeg, aromatic phenol-ethers, essential oils, monoterpenes